EMPOWERING WOMEN IN BHAGAT’S FICTION - Khubwani, Manju; Naidu, Rajshree (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper critically examines the theme of women empowerment in the literary works of Chetan Bhagat, focusing on his popular novels such as Revolution 2020, Half Girlfriend, One Indian Girl, and The Girl in Room 105. Bhagat, often seen as a voice for India’s youth, provides a narrative space where women assert autonomy, question societal norms, and negotiate complex identities. While his male protagonists often drive the plots, Bhagat's female characters are not merely passive recipients of action; they are often catalysts of personal and social transformation. Through close textual analysis, the paper explores how Bhagat portrays women in conflict with patriarchy, tradition, and class boundaries, yet striving for independence, education, and career fulfillment. Novels like One Indian Girl foreground the internal dilemmas of a modern woman caught between professional ambition and romantic expectations, whereas characters like Aarti (Revolution 2020) and Riya (Half Girlfriend) represent nuanced struggles for voice and choice. The paper also discusses Bhagat’s narrative strategies—such as first-person female perspectives, confessional tones, and realist settings—that enhance the relatability of these stories. By blending popular fiction with themes of gender justice, Bhagat opens dialogues about female agency in a society undergoing cultural shifts. The study argues that while his works have their limitations, they play a significant role in normalizing feminist discourse within mainstream Indian literature. The paper concludes that Bhagat’s fiction, despite its commercial orientation, contributes meaningfully to the project of women’s empowerment and socio-cultural reform in contemporary India.